Shadows of the Ancestors - Mbamali, Onyechi (Macmillan Nigeria Publishers Ltd, 2009)
This play mirrors generational conflicts and ideological perspectives in a period of transition from an old regime. A custom of programmed succession to kingship is threatened by the romantic diversions of a young crown prince and his chosen band of fellow radical youth...
Keywords: Plays